Validation study of urinary metabolites as potential biomarkers for prostate cancer detection. (May 2012) - Gamagedara, Sanjeewa; Kaczmarek, Anthony T; Jiang, Yongqing; Cheng, Xiaoling; Rupasinghe, Maduka; Ma, Yinfa
Background: Urinary metabolomic profiles have recently drawn a lot of attention owing to a debate regarding their possible role as potential clinical markers for prostate cancer. In this study, levels of proline, kynurenine, uracil and glycerol-3-phosphate in 126 patients with genitourinary malignancies were analyzed using a validated method and compared with no evidence of malignancy.Results: The statistical results showed that these biomarkers cannot differentiate prostate cancer from no evidence of malignancy or from other related cancer types, such as bladder cancer. In addition, there was no significant difference in biomarker levels for T1 stages, T2 stages and Gleason scores <7, ≥7. From the correlation study, results showed/demonstrated that age or serum prostate-specific antigen levels do not influence these metabolite concentrations in urine. However, the strong correlation between these metabolites and urinary creatinine concentrations implies that their occurrence is mainly due to renal excretion.Conclusion: This detailed study shows that the aforementioned urinary metabolites are not reliable biomarkers for prostate cancer detection or for differentiating the aggressiveness of prostate cancer.